Pengaruh Financial Technology dan Pemanfaatan Sistem Informasi Akuntansi Terhadap Kinerja Keuangan UMKM Kuliner di Foodcourt Medan Estate - Leoni Tandra; Susan Grace V Nainggolan (Politeknik Ganesha Medan, 2026)
This study aims to analyze the effect of financial technology (fintech) and the utilization of accounting information systems (AIS) on the financial performance of culinary MSMEs at Foodcourt Medan Estate, Deli Serdang Regency. The research background highlights the low adoption of digital technology among MSMEs, both in financial transactions and accounting records, which results in fluctuating revenues, low liquidity ratios, and less credible financial reports. This condition reflects a gap between the potential of digital technology and its actual implementation in practice. A quantitative approach was employed, with a population consisting of all culinary MSMEs at Foodcourt Medan Estate and a sample of 220 respondents determined using the Slovin formula. The research instrument was tested for validity and reliability, and the data were analyzed using multiple linear regression with SPSS version 25. The findings reveal that fintech has a positive and significant effect on financial performance, with a regression coefficient of 0.368 and t value of 9.550 (sig. 0.000). AIS also shows a positive and significant effect, with a regression coefficient of 0.193 and t value of 5.455 (sig. 0.000). Simultaneously, both variables significantly influence financial performance, as indicated by an F value of 78.264 (sig. 0.000). The coefficient of determination (R²) of 0.419 indicates that 41.9% of financial performance variation is explained by fintech and AIS, while the remaining 58.1% is influenced by other factors. These findings emphasize the importance of enhancing digital literacy, accounting competence, and trust in technology to strengthen MSME competitiveness in the digital era.